The Situation of Mass Communication Activities on Food Safety and Social Effects Regarding Food Safety in Hanoi, Vietnam in the Current Period - Mai, Linh (Journal of Posthumanism, 2025)
Food safety has been a matter of concern to Vietnamese society, especially in the context of the Covid-19 pandemic. It is essential for people to choose safe ingredients, which help build the body’s resilience. Therefore, the responsibility of mass communication to the community is to raise awareness and shift the behavior of the public towards observance of food safety regulations. This study points out the contributions of mass communication to detecting food safety violations, providing information on handling food safety violations, motivating people to comply with regulations through advisory, guiding, and orientation information. At the same time, the study includes an analysis of mass communication’s influence on shifting the public’s cognition and behavior. Plus, several recommendations are proposed to enhance the quality of communication on food safety such as publishing timely and accurate information; improving guiding information; expanding the network of collaborators, hotlines to report violations; coordinating with the authorities to build programs and categories of communication on food safety. Research findings are based on the survey data involving 300 residents in Hoan Kiem District and Van Dinh town, Ung Hoa District, Hanoi in August 2020.